Applicability of Core–Shell Hybridization Approach Using Natural and Recycled Aggregate Concrete - Ji-Hyun Kim; Andres Salas-Montoya; Young-Chan Kim; Chul-Woo Chung (International Journal of Concrete Structures and Materials)
Abstract The aim of this research is to propose a novel technique to improve the performance of structural concrete member using recycled aggregate by creating a core–shell hybrid concrete instead of intermixing natural aggregate concrete with recycled aggregate concrete. The technique involves layered casting of a recycled aggregate concrete with natural aggregate concrete, either as a core or as a shell, to prove whether this core–shell hybridization approach has a potential to facilitate the utilization of recycled aggregate for structural concrete. Various core–shell combinations were made using w/c 0.3 and 0.5 concretes, and compressive strength, elastic modulus, and chloride ion diffusivity of the hybrid specimens were measured. This paper also investigated the effects of two-stage mixing approach on properties of recycled aggregate concrete and hybrid concrete. It was found that placing stronger NAC at the outer shell provided higher compressive strength and elastic modulus of core–shell hybrid concrete. Placing NAC at the outer shell also provided lower chloride ion diffusivity as it acted as a diffusion barrier. It is recommended to place a stronger and more durable natural aggregate concrete in the shell to have better mechanical properties and durability. A synergetic effect of hybridization was observed from elastic modulus, not from the compressive strength. It was also found that compressive strength and elastic modulus of core–shell hybrid concrete were successfully estimated using those of control concrete specimens.